Prognostic value of venous thromboembolism in patients with advanced pancreatic cancer: a systematic review and meta-analysis - Su, Kaifeng; Duan, Ruifeng; Wu, Yang (Frontiers in Oncology, 2024)
Objective This study aimed to investigate the relationship between the incidence of VTE and the prognosis of patients with advanced pancreatic cancer, as there is currently a lack of systematic research on this topic, despite the prevalence of venous thromboembolism (VTE) in patients with pancreatic cancer. Methods Databases including PubMed, Embase, Web of Science, and Cochrane Library were searched until April 9, 2023, to identify studies that explored the relationship between VTE and the prognosis of advanced pancreatic cancer. Duplicate publications, studies without full text or sufficient information for data extraction, animal experiments, reviews, and systematic reviews were excluded. The extracted data were analyzed using STATA 15.1. Results The pooled results indicated a significant association between the incidence of VTE and poorer overall survival (HR=1.38, 95% CI: 1.24 - 1.53, p < 0.001) and disease-free survival (HR=2.42, 95% CI: 1.94 - 3.04, p < 0.001) among patients with advanced pancreatic cancer. Additionally, early VTE showed a significant impact on overall survival (HR=2.03, 95% CI: 1.33 - 3.12, p = 0.001), whereas late VTE did not demonstrate a significant association with poor overall survival (HR=1.22, 95% CI: 0.96 - 1.54, p = 0.099). Conclusions This study found that advanced pancreatic cancer patients with VTE had poorer overall and disease-free survival than those without. Meanwhile, the patients with early VTE had a significantly poorer prognosis, whereas late VTE did not. The findings highlight the importance of timely detection of VTE for patients with advanced pancreatic cancer patients and offer a partial theoretical basis for future clinical endeavors. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023427043, identifier CRD42023427043.